Fighting Another’s War: Imperialist Projections on the Victorian Novel’s Continent - Tamara Wagner (Cahiers Victoriens et Edouardiens)
Set in the late-1840s, Wilkie Collins’s sensation novel The Woman in White uses the Italian War of Independence as more than a background. Instead, it becomes a renegotiation of both Britain’s involvement—diplomatic or cultural as well as on the battlefield—in the wars waging in Europe at the time and, by metaphorical extension, its own “little wars” in the colonies. The “internal colonisation” practised by the Austrian-Hungarian Empire alternately serves as a convenient projection and a mirror-image of self-accusation. The proposed paper traces the representation of European wars in nineteenth-century British fiction. They were seen as a threat, spilling over into Britain, as bringing in competing flows of refugees, and most importantly perhaps, as demanding a rethinking of imperialist legacies of guilt. The focus will be on the representation of the Italian struggle for independence in novels of the 1860s by Wilkie Collins, Mary Elizabeth Braddon (especially the Austrian villains in The Black Band and Run To Earth), and Meredith’s Emilia in England, later reprinted as Sandra Belloni, and the sequel, Vittoria. Yet it also forms a vital undercurrent in Dickens’s Little Dorrit, a novel that fascinatingly brings in references to colonial guilt produced by the opium trade in China and the second opium war, which was waging when the novel was still being serialised, the Crimean War, and the Risorgimento. In this, it testifies perhaps most insistently to the cultural pervasiveness of Europe’s wars in the Victorian novel.